Assessing the reliability of retrospective reports of adverse childhood experiences among adolescents with documented childhood maltreatment - Pinto, Ricardo (2014)
The literature suggests that childhood maltreatment is related to a higher probability of developing psychopathology and disease in adulthood. However, some authors have questioned the reliability of self-reports of maltreatment, suggesting that psychopathology at the time of evaluation affects self-reports. We evaluated the reliability of the self-reports of 79 young adults who were identified in childhood by Child Protective Services by comparing two moments of evaluation. Psychological and physical symptoms were tested to evaluate their interference with the reports. We found good to excellent agreement, with no significant correlation between the changes in self-reported experiences and the changes in physical and psychological symptoms, suggesting that the reliability of reports is not related to the health state at the time of the report.